2015
DOI: 10.1136/bjsports-2015-095100
|View full text |Cite
|
Sign up to set email alerts
|

Is higher serum cholesterol associated with altered tendon structure or tendon pain? A systematic review

Abstract: BackgroundTendon pain occurs in individuals with extreme cholesterol levels (familial hypercholesterolaemia). It is unclear whether the association with tendon pain is strong with less extreme elevations of cholesterol.ObjectiveTo determine whether lipid levels are associated with abnormal tendon structure or the presence of tendon pain.MethodsWe conducted a systematic review and meta-analysis. Relevant articles were found through an electronic search of 6 medical databases—MEDLINE, Cochrane, AMED, EMBASE, Web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 63 publications
2
83
1
3
Order By: Relevance
“…While both types of diabetes expose the body to hyperglycaemia, other factors such as insulin resistance, adiposity and elevated lipids, more commonly found in individuals with type 2 diabetes,72 are associated with tendon pathology 5 75 76. It was not possible to compare participants by type of diabetes as too few studies included people with type 1 diabetes only.…”
Section: Discussionmentioning
confidence: 99%
“…While both types of diabetes expose the body to hyperglycaemia, other factors such as insulin resistance, adiposity and elevated lipids, more commonly found in individuals with type 2 diabetes,72 are associated with tendon pathology 5 75 76. It was not possible to compare participants by type of diabetes as too few studies included people with type 1 diabetes only.…”
Section: Discussionmentioning
confidence: 99%
“…The Cochrane Colloquium, 2014). Prognostic factors were high baseline disability,28 long duration of symptoms prior to intervention,2 28 higher initial pain intensity,28 older age,28 OA,2 previous treatment2 and general health issues such as diabetes mellitus29 and hypercholesterolaemia 30 31. Lievense et al 2 found that patients with osteoarthritis were 4.8 times more likely to have symptoms at 1 year, while patients that had previously received injections for GTPS were 2.7 times more likely to recover at 5 years.…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review18 demonstrated that individuals with an adverse lipid profile might have an increased risk to cause tendon pathologies including rotator cuff tear. The meta-analysis revealed higher serum levels of total cholesterol (TC), low-density lipoprotein cholesterol and triglycerides as well as lower levels of high-density lipoprotein cholesterol in those with the Achilles tendinopathy or rotator cuff tears 18. In addition, chronic alcohol consumption has also shown to be associated with the prevalence of rotator cuff tears.…”
Section: Epidemiology Of Rotator Cuff Tearmentioning
confidence: 99%